Soy polysaccharide maintains colonic homeostasis to protect from dextran sulphate sodium-induced colitis by modulating gut microbiota and intestinal epithelial regeneration - Nana Zhang; Jianlin Liu; Weiyue Zhang; Xinxin Guo; Shuying Li; Hongtai Zhang; Minjie Wang; Bei Fan; Fengzhong Wang (Food Science and Human Wellness)
Soy polysaccharide (SP) has been reported to possess the properties of modulating gut microbiome diversity. Here, we aimed to explore the protective effects of SP against dextran sulphate sodium (DSS)-induced colitis. Pre-treatment with SP at a dosage of 400 mg/kg·day alleviated colitis symptoms, preventing the weight loss and colon shorten. SP suppressed DSS-induced inflammatory response and enhanced M1 to M2 macrophage polarization. Further investigation showed that SP significantly promoted the regeneration of crypt and the expansion of goblet cell production. In addition, bacterial 16S rRNA sequencing analysis showed that SP modulated the composition of fecal microbiota, including selectively increasing Lactobacillus relative abundance. Notably, SP treatment enriched the production of Lactobacillus-derived lactic acid, which was sensed by its specific G-protein-coupled receptor 81 (Gpr81)/Wnt3/β-catenin signaling, and promoted the regeneration of intestinal stem cells. Fecal microbiome transplantation demonstrated that intestinal flora partially contributed to the beneficial effects of SP on preventing against colitis. In conclusion, SP exhibited the protective effects against colitis, which could be partly associated with modulating the composition of gut microbiota and enrichment of lactic acid. This study suggests that SP has potential to be developed as nutritional intervention to prevent colitis.